La legión - Scarrow, Simon (Scarrow, Simon. Roman Legion series., 2015)
Trouble is brewing in Egypt. Rebel gladiator Ajax and his men have been posing as Roman soldiers and attacking naval bases, merchant vessels and villages. Prefect Cato and Centurion Macro have been charged with the task of tracking down the renegade warrior before the problem gets out of control.